Derivation of stress intensity factor for a cracked plate with an integrated piezoelectric actuator - Abuzaid, Ahmed; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim (2014)
The purpose of this work is to derive an analytical model under linear-elastic fracture mechanics (LEFM) to represent the effect of piezoelectric actuation on energy release rate and Mode I stress intensity factor for a plate subjected to a uniform biaxial tension stress . The piezoelectric actuator is inducing a local force above the crack area via an external voltage to reduce the stress singularity around the crack tip. The results indicate that the stress intensity factor decreases with the application of the piezoelectric actuator voltage.